Measuring tooth size discrepancies using Bolton analysis: a comparative cross-sectional study among major ethnicity in Malaysia - Aida Nur Ashikin Abd Rahman; Siti Adibah Othman; Anand Marya (BMC, 2023)
Abstract Background The Bolton analysis is one of the commonly used tooth size analysis or diagnostic tools in deriving a treatment plan for orthodontic patients. Many studies have indicated and concluded that normal measurements for one group should not be considered normal for other ethnic groups. The aims and objectives of this study were to investigate the applicability of Bolton's ratios in the orthodontic population of Malaysian main ethnics, Malay, Chinese, and Indians. Comparisons were made in terms of size and distribution of tooth size discrepancy in the Malaysian orthodontic population and the findings were converted in terms of millimeters. Methods Hundred fifty pre-orthodontic study casts comprised of 52 Malay, 54 Chinese, and 44 Indian patients were selected. Digital calipers (Fowler Pro-Max) linked to Hamilton Tooth Arch Software were used to measure the tooth width and ratios. Statistical analysis was carried out to test for gender differences (independent t-test), to identify the effects of malocclusion and ethnic groups (Two-way ANOVA), and to compare the means of the current study with Bolton's standards (one sample t-test). Results This study showed that there was no significant difference between the genders of the sample of each ethnicity. There was no correlation found between ethnic groups and malocclusion classes. There was a significant difference when comparing Bolton values with the Malay sample for both ratios. It was found that more Malay subjects presented with maxillary excess contrary to Chinese and Indians who presented more maxillary deficiency for the anterior and overall ratio. Conclusion There was a significant difference found between the TSD of the three major ethnicities in Malaysia. The Bolton standards can be applied to Malaysian Chinese and Indians but not to Malays orthodontic populations for both anterior and overall ratios. Subsequently, a specific standard should be used for the Malays orthodontic population. It was found that more Malay subjects presented with maxillary excess contrary to Chinese and Indians who presented more maxillary deficiency for the anterior and overall ratio.